If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + -6y) = 0 (4x * 2 + -6y * 2) = 0 (8x + -12y) = 0 Solving 8x + -12y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12y' to each side of the equation. 8x + -12y + 12y = 0 + 12y Combine like terms: -12y + 12y = 0 8x + 0 = 0 + 12y 8x = 0 + 12y Remove the zero: 8x = 12y Divide each side by '8'. x = 1.5y Simplifying x = 1.5y
| 9x-8=90 | | 14-2n=-6 | | 7x+9+9x-8=180 | | -3/8x=11 | | x^2+1/x^2-2=0 | | 10x-2+3x-3=180 | | 3x+9+3x-3=180 | | 3x+2y- 4z= -7 | | -18.473=1.3(8-m) | | 10x-2+3x+9=180 | | 3x+ 2y-4z=-7 | | 2x+4/2x^2+8x+8 | | 3x+2y-4z =-7 | | 3x + 2y - 4z = -7 | | 14x+2+10x+50=90 | | ((1-2x)/(3-x))=((x-2)/(3x-1)) | | (5p^3-6p^3+7p-4)-(-8p^2-6p+3+p^3)= | | 14x+2+10x+50=180 | | -21=46+19(-6b) | | (4x+2x)(3x+2x)=480 | | 16x^2+4(x^4-4x^2-4x^2+16)-64=0 | | 4x+2x(3x+2x)=480 | | 69=8c-3 | | 6e-1=11 | | -3t^2-14t+4=0 | | x^2*14x+40=0 | | 8x^2+25x-200=0 | | 20x=192 | | 4x^2+25-200=0 | | ((2x-1)/(x+2))+((x+2)/(2x-1))=(10/3) | | 8x^2-7x=4x-14x^2 | | 0.06/0.02 |